Three-Port Full-Bridge Cell for Multilevel Converters with Battery Energy Storage - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2019)
Utility-scale Battery Energy Storage Systems (BESS) have increased rapidly during the last years providing grid support for variable renewable energies, operating reserve, and any other possible ancillary service. BESS can be connected to the MV grid through conventional converters such as two-level or NPC, or through multilevel converters such as CHB or MMC. Multilevel converters do not require LV/MV transformer or ac filter, which increases the efficiency and reduces the footprint and cost. Different cell topologies for multilevel converters have been proposed in order to interface the batteries with the ac side, where the key performance indicators are the battery current peaks, number of semiconductors, footprint, efficiency and cost. This paper proposes a three-port full-bridge cell (TPC) to connect the battery in multilevel converters through a Model Predictive Control. This cell adds passive elements that decouple the battery from the cell capacitor, avoiding the battery current peaks, downsizing the cell capacitor and improving the footprint. Simulation and experimental results show that the power flow between batteries and the grid can be controlled keeping the cell capacitors balanced and ensuring the best battery treatment. © 2019 IEEE.